Strategy and Tactics of Political Activity of the Ukrainian National Democratic Union in the first half of the 1930s - Oksana Potikha (Науковий вісник Чернівецького національного університету імені Юрія Федьковича. Історія, 2017)
The article analyzes the features of changing the political strategy and tactics of one of the toppolitical parties of Western Ukraine of the Inter-War Period - the Ukrainian National Democratic Union. The aggravation of the Polish-Ukrainian contradictions and the Soviet policy of destroying the Ukrainian heritage in the Dniprоregion duringthe early 1930s prompted the Ukranian National Democratic Union  to search for new methods of activity and caused the political line of the party to change in the direction of finding ways of mutual understanding with the Polish authorities. In the second half of 1930s the slogans of independence and national unitywere excludedfrom the party's arsenal and replaced by their demand for national-territorial autonomy for all Ukrainian lands in Poland. The anti-Ukrainian terror in Soviet Ukraine denuded theUkranian National Democratic Unionof hopes for the growth of National forces in the Dniprоregion. These circumstances movedthe party leaders of the National Democrats forward in mending thePolish-Ukrainian relations.